O início da trajetória ocupacional: quais são seus determinantes? - Marta Santos Sales; Gustavo de Melo; Danielle Cireno Fernandes (Ciências Sociais Unisinos)
This work is about the occupational status of the first job, analyzing the effect of socioeconomic inheritance, gender and age of the individual on status. The grounding starts from the area of social stratification of Sociology. The study was composed of a representative sample of the Brazilian population and an intentional sample of young people from the metropolitan area of Belo Horizonte, concomitantly. The results problematize the inequalities related to the processes of work and education in adolescence and the beginning of the occupational trajectory of the individuals.